Primer aislamiento de Clostridium botulinum en Costa Rica - Gamboa, María del Mar (Universidad de Costa Rica, 1993)
Among 60 isolates from Costa Rican isolates, one shared biochemical and chromatographic correspondence with C. botulinum A,B,F group (proteolytic) and produced a toxin which could be identified as belonging lo the A type when mouse neutralization tests were carried out employing both polyvalent and type Specfic anusera